FREKUENSI DAN PENYEBARAN ALEL GOLONGAN DARAH A B O SISWA SMUN I SUKU BANGSA MELAYU DI KECAMATAN RUPAT KABUPATEN B ENGKALIS RIAU - Darmawati '; Evi Suryawati; Edi Suhendri (Biogenesis, 2005)
The objective of this research was to examine the allele frequency and dissemination A BO blood group of SMUN  I Melayu student, Bengkalis regency. This research have done on November 2001 – February 2002. Survey method was used in this study. The parameter observation was allele frequency  IA, lB, and IO. Data  analyzed  by  using Hardy  Weinberg  Law  and  chi  square.  The results shows that  the allele frequency IA (0,152), lB (0,326), 1° (0,522). There was no equilibrium in allele dissemination.   Kay words : ABO blood group, dissemination, equilibrium. SMUN I Bengkalis regency.